Effects of Public Expenditure On Economic Development In Nigeria. - Ewa, Uket Eko; Okoi, Christopher Ubi; Okoi, Christopher Ubi; Okoi, Christopher Ubi (Advances in Social Sciences Research Journal, 2018)
This study examined the effect of public expenditure on economic development in Nigeria for the period 2000–2015. Ordinary Least Square (OLS) multiple regression model was employed on the perceived causal relationship between public expenditure and economic development. The study revealed that capital expenditure on Economic Services and recurrent expenditure on administration exerted positive and insignificant effect on unemployment rate in Nigeria while public expenditure on social and community service exerted negative and insignificant effect on unemployment rate in Nigeria. Also the study revealed that capital expenditure on Economic Services and Social and Community Services exerted positive and significant effect on private investment in Nigeria while recurrent expenditure on administration exerted negative and significant effect on private investment in Nigeria. In all, the study revealed a significant impact of public expenditure on GDP, unemployment rate and private investment in Nigeria for the period 2000-2015. It is recommended amongst others that capital and recurrent expenditures on economic services should be directed mainly to the agricultural sector. This will stimulate activities in the economic sectors and, perhaps, reverse the negative effect on economic development.